2021
DOI: 10.7759/cureus.20175
|View full text |Cite
|
Sign up to set email alerts
|

Post-chemotherapy Changes in Bone Marrow in Acute Leukemia With Emphasis on Detection of Residual Disease by Immunohistochemistry

Abstract: In acute leukemia, the leading cause of treatment failure is disease relapse leading to a low level of complete remission and short overall survival. Post-chemotherapy marrow examination gives vital clues regarding treatment response and marrow regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
2
0
0
Order By: Relevance
“…Presence of cluster of immature cells is usually concerning for residual leukemic blasts. Ayyana, et al reported small and large clusters of immature cells are present in 12 out of 18 (66.7%) acute leukemia patients in sustained remission [15]. Similar to their observations, we found three cases in our study where small and large clusters of immature B-cells are present but proven to be B-ALL in remission without MRD by MFC and ClonoSEQ.…”
Section: Phenotypic Features Of B-all Mrdsupporting
confidence: 91%
“…Presence of cluster of immature cells is usually concerning for residual leukemic blasts. Ayyana, et al reported small and large clusters of immature cells are present in 12 out of 18 (66.7%) acute leukemia patients in sustained remission [15]. Similar to their observations, we found three cases in our study where small and large clusters of immature B-cells are present but proven to be B-ALL in remission without MRD by MFC and ClonoSEQ.…”
Section: Phenotypic Features Of B-all Mrdsupporting
confidence: 91%
“…A study found that only 2.6% of patients had bone marrow fibrosis after induction therapy. Similarly, the bone marrow fibrosis of the patients in our study returned to normal except for one patient (5.5%) [14,26].…”
Section: The European Researchsupporting
confidence: 68%